Measurement of Efficiency and Productivity of Zakat Institutions in Indonesia using Data Envelopment Analysis and the Malmquist Productivity Index - Selvia Rustyani; Suherman Rosyidi (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
This study aims to measure the level of efficiency and productivity of zakat institutions in Indonesia.Quantitative research using the methods of Data Envelopment Analysis (DEA) and the Malmquist Productivity Index (MPI). There are six Amil Zakat (LAZ) institutions in Indonesia, namely Yayasan Dana SosialAl-Falah (YDSF), Al-Azhar Peduli Ummat, Aksi Cepat Tanggap (ACT), Yayasan Rumah Yatim Arrohman Indonesia,Pos Kemanusiaan Peduli Ummat (PKPU), and Rumah Zakat Indonesia, with 2014–2016 annual data as the number of DMUs (decision making units). This study uses an intermediation approach in determining the variables.The input variables of this research are Collected Funds (X1), Total Costs (X2), and Amil Acceptance (X3), while the Output variables are Funds Distributed (Y1) and Total Assets (Y2).There were two LAZs that experienced inefficiencies in 2014 and 2015, namely LAZ YDSF and ACT. Meanwhile, in 2016, all LAZs achieved optimal levels of efficiency. The results of the MPI analysis show that in the first year two LAZs experienced a decline in productivity, namely LAZ Al-Azhar and PKPU. The other four LAZs sawan increase in productivity, namely LAZ YDSF, ACT, Rumah Yatim, and Rumah Zakat. In the second year, three LAZsexperienced a rise in productivity, namely LAZ Al-Azhar, PKPU, and Rumah Zakat, while the other three LAZs experienced a decrease in productivity, namely LAZ YDSF, ACT, and Rumah Yatim.